STUDI KAJIAN HASIL TANGKAPAN SAMPINGAN (BYCATCH DAN DISCARD) ALAT TANGKAP PAYANG PADA KAPAL KM MAHKOTA DI PELABUHAN PERIKANAN SUNGAILIAT PROVINSI BANGKA BELITUNG - Irwan Sinaga; Nofrizal Nofrizal; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT        Payang is a trawler tug that has a small pocket size. This makes the payang fishing gear not selective about the size of the fish and the types of fish that are targeted by the catch. If this fishing gear is left then it will have a negative impact on the continuation of fish resources, especially where the fishing gear is operated. The purpose of this study is to calculate the composition and proportion of the main catches (main catch), bycatch and bycatch. It is hoped that this research can illustrate the amount of fish stock pressure available at the Payang fishing gear. The method used is a survey method that directly measures the fishing gear and identifies the catch of the payang fishing gear. Based on the percentage of the composition, the type of payang catches consists of 8 types. Based on the composition, the types of payang catches consist of 8 types of individuals, consisting of 2 main catches with a percentage of 25%, 5 types of bycatch with a percentage of 62.5% and 1 type of catch catch with a percentage of 12.5%. This study also found that the payang also caught fish with a size below maturity, namely yellow strait fish (Selaroides leptocepis) with a percentage of fish below the adult size caught 28%, bentong strait fish (Crumenopthaimus selar) with the percentage of fish below the adult size caught 25%, and even mackerel (Rastrelliger brachysoma) reaches 67.25% of fish below the adult size caught. Therefore, it can be concluded that Payang fishing gear even though it is a fishery fishing gear that has enough potential to change the structure of aquatic biodiversity.Keywords: bycatch, discard, payang, fish resources, main catch.